MORPHOMETRIC RELATIONSHIP OF THE INDIAN SCAD, DECAPTERUS RUSELLI (RUPPELL, 1830) FROM MAHARASHTRA WATERS, NORTHWEST COAST OF INDIA - Poojary, Nalini; Sundaram, Sujit (Journal of Indian Fisheries Association, 2014)
The relationship of various morphometric characters of Decapterus russelli from Maharashtra water weres studied. The coefficient of correlation (r) for various morphometric characters ranged from 0.880 to 0.983 indicating high degree of relationship among the characters compared. Analysis of 15 morphometric characters revealed that the fork length had the fastest growth rate with reference to total length while snout length had fastest growth rate with reference to head length. Fin formula for D. russelli from Mumbai waters could be written as: B.6, D.8 | 1/27-31 + i, P.20 â€“ 22, V.1/5,A.2 | 1/25-28+i,C.17-19, BS. 30-41, LI. 37-61. Â Key words: Morphometric relationships, meristic studies, Decapterus russelli, Carangids, Indian scad, Maharashtra.